2014
DOI: 10.1063/1.4869564
|View full text |Cite
|
Sign up to set email alerts
|

Transport characteristics of a superconductor–ferromagnet composite

Abstract: The transport properties of a composite consisting of the microparticles of superconductor MgB2 and nanopowder of manganite La0.7Sr0.3MnO3 (LSMO) were studied. It was found that when the amount of the ferromagnet component in the composite was above 10% by volume, a sharp increase in the resistivity of the composite occurred. This is caused by the disruption of percolation paths through the magnesium diboride microparticles, thus leading to the formation of a network of superconductor-ferromagnet-superconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Kalcheim et al 240 epitaxially grew LCMO films on superconducting Pr 1.85 Ce 0.15 CuO 4 , and they found a long-range penetration of superconductivity into the HM LCMO by scanning tunneling spectroscopy. Kononenko et al 241 also investigated the transport properties of composites consisting of MgB 2 superconductor microparticles and La 0.7 Sr 0.3 MnO 3 (LSMO) manganite nanopowders. They found that the disruption of the percolation path through the MgB 2 particles caused the resistivity of the composite to increase, resulting in a network of SFS junctions.…”
Section: Josephson Junctionsmentioning
confidence: 99%
“…Kalcheim et al 240 epitaxially grew LCMO films on superconducting Pr 1.85 Ce 0.15 CuO 4 , and they found a long-range penetration of superconductivity into the HM LCMO by scanning tunneling spectroscopy. Kononenko et al 241 also investigated the transport properties of composites consisting of MgB 2 superconductor microparticles and La 0.7 Sr 0.3 MnO 3 (LSMO) manganite nanopowders. They found that the disruption of the percolation path through the MgB 2 particles caused the resistivity of the composite to increase, resulting in a network of SFS junctions.…”
Section: Josephson Junctionsmentioning
confidence: 99%